The fuzzy systems handbook a practitioner's guide to building, using, and maintaining fuzzy systems - Cox, Earl (AP Professional, 1999)
This edition provides a comprehensive introduction to fuzzy logic, and leads the reader through the complete process of designing, constructing, implementing, verifying and maintaining a platform-independent fuzzy system model. The book has been extensively revised to bring the subject up-to-date, and features two new chapters: "Building and Using Fuzzy Cognitive Map Models" and "Building ME-OWA Models."